CIP2A Causes Tau/APP Phosphorylation, Synaptopathy, and Memory Deficits in Alzheimer's Disease - Yang-Ping Shentu; Yuda Huo; Xiao-Long Feng; James Gilbert; Qing Zhang; Zhen-Yu Liuyang; Xiu-Lian Wang; Guan Wang; Huan Zhou; Xiao-Chuan Wang; Jian-Zhi Wang; You-Ming Lu; et al. (CELL PRESS, 2022)
Protein phosphatase 2A (PP2A) inhibition causes hyperphosphorylation of tau and APP in Alzheimer's disease (AD). However, the mechanisms underlying the downregulation of PP2A activity in AD brain remain unclear. We demonstrate that Cancerous Inhibitor of PP2A (CIP2A), an endogenous PP2A inhibitor, is overexpressed in AD brain. CIP2A-mediated PP2A inhibition drives tau/APP hyperphosphorylation and increases APP beta-cleavage and A beta production. Increase in CIP2A expression also leads to tau mislocalization to dendrites and spines and synaptic degeneration. In mice, injection of AAV-CIP2A to hippocampus induced AD-like cognitive deficits and impairments in long-term potentiation (LTP) and exacerbated AD pathologies in neurons. Indicative of disease exacerbating the feedback loop, we found that increased CIP2A expression and PP2A inhibition in AD brains result from increased A beta production. In summary, we show that CIP2A overexpression causes PP2A inhibition and AD-related cellular pathology and cognitive deficits, pointing to CIP2A as a potential target for AD therapy.